2010
DOI: 10.1038/hr.2010.26
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal blood pressure variation and sympathetic activity

Abstract: Blood pressure changes occurring over a 24-h period are under behavioral, humoral and reflex regulation. The sympathetic nervous system modulates blood pressure variation by affecting cardiac output and peripheral vascular resistance. This paper reviews evidence for the relationship between adrenergic neural drive and blood pressure as measured by direct and indirect approaches. This paper also reviews the sympathetic activity associated with increased 'in-office' and 'out-of-office' blood pressure, that is, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 39 publications
2
51
1
8
Order By: Relevance
“…22 The shorter, ultradian rhythms are more dependent on sympathetic activity caused by external and behavioral stimuli. 23 The most commonly used marker of BP rhythmicity is nocturnal dipping that has been shown to be an important independent risk factor for cardiovascular disease. 11,24 Our results confirm that the nighttime dipping of BP is reduced in children born SGA, as already found in prepubertal, low birth weight children, 25,26 and in children with primary 27 or secondary hypertension attributed to chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…22 The shorter, ultradian rhythms are more dependent on sympathetic activity caused by external and behavioral stimuli. 23 The most commonly used marker of BP rhythmicity is nocturnal dipping that has been shown to be an important independent risk factor for cardiovascular disease. 11,24 Our results confirm that the nighttime dipping of BP is reduced in children born SGA, as already found in prepubertal, low birth weight children, 25,26 and in children with primary 27 or secondary hypertension attributed to chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…These changes in BP are largely attributed to mental and physical activities, and the sympathetic nervous system has a crucial role in the generation of diurnal BP variation. 9,[13][14][15] It has been shown that diurnal changes in BP coincide with changes in heart rate and the levels of plasma and urinary catecholamines. [13][14][15][16] It also has been shown that BP is high during nighttime working hours and low during daytime sleeping hours in shift workers, although the dip in BP during sleeping hours may be attenuated at the beginning of the night shift.…”
Section: Diurnal Bp Variation In Relation To Mental and Physical Actimentioning
confidence: 99%
“…9,[13][14][15] It has been shown that diurnal changes in BP coincide with changes in heart rate and the levels of plasma and urinary catecholamines. [13][14][15][16] It also has been shown that BP is high during nighttime working hours and low during daytime sleeping hours in shift workers, although the dip in BP during sleeping hours may be attenuated at the beginning of the night shift. 17,18 These results indicate that the endogenous clock has a minor role in the generation of BP variation associated with the awake and sleep cycle.…”
Section: Diurnal Bp Variation In Relation To Mental and Physical Actimentioning
confidence: 99%
“…6 Nevertheless, there is growing evidence that sympathetic nerve activity contributes importantly to BP variability and the diurnal BP profile. 7,8 Normally, BP decreases during sleep by at least 10% of the awake value, and occurrence of 'dipping' correlates directly with the amount of deep sleep and inversely with indices of sleep fragmentation. 9 There has been great interest in the mechanisms and clinical significance of the 'dipper' or 'non-dipper' pattern of ambulatory BP profiles.…”
Section: Introductionmentioning
confidence: 99%